Dr. Enio Ilinoiu — Deep Plane Facelift — Bucharest - Ilinoiu, Enio (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Enio Ilinoiu, practicing in Bucharest, Romania. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003413; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; romania; bucharest